The Influence of Digital Literacy on Students' Critical Thinking Skills - Didit Darmawan; Mas Ummu Chasbiyah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study examines the impact of digital literacy on the critical thinking skills of elementary school students (Madrasah Ibtidaiyah, MI). With the rapid development of digital technology, the use of the internet and digital devices has become increasingly widespread in daily life, including in the education sector. However, not all students are able to use digital information critically and effectively, making digital literacy a crucial competency that must be developed from an early age. A qualitative approach using a literature review method was applied in this study. Data was collected from various sources, such as books, journals, and other academic publications, and then analyzed using content analysis techniques. The results of the study of ten research articles indicate that digital literacy, reading literacy, interest in reading, interest in learning, and independent learning are interrelated and have a positive influence on the critical thinking skills of elementary school students. Digital literacy facilitates students in accessing, understanding, and evaluating information effectively, while the implementation of literacy-based learning supported by digital media is also capable of encouraging student engagement and participation in the learning process.